Tuning the Electrochemical Performance of Titanium Carbide MXene by Controllable In Situ Anodic Oxidation - Tang, Jun; Mathis, Tyler S.; Kurra, Narendra; Sarycheva, Asia; Xiao, Xu; Hedhili, Mohamed N.; Jiang, Qiu; Alshareef, Husam N.; Xu, Baomin; Pan, Feng; Gogotsi, Yury (Angewandte Chemie (International ed.), 2019)
MXenes are a class of two‐dimensional (2D) transition metal carbides, nitrides and carbonitrides that have shown promise for high‐rate pseudocapacitive energy storage. However, the effects that irreversible oxidation have on the surface chemistry and electrochemical properties of MXenes are still not understood. Here we report on a controlled anodic oxidation method which improves the rate performance of titanium carbide MXene (Ti3C2Tx, Tx refers to ‐F, =O, ‐Cl and ‐OH) electrodes in acidic electrolytes. The capacitance retention at 2000 mV s−1 (with respect to the lowest scan rate of 5 mV s−1) increases gradually from 38 % to 66 % by tuning the degree of anodic oxidation. At the same time, a loss in the redox behavior of Ti3C2Tx is evident at high anodic potentials after oxidation. Several analysis methods are employed to reveal changes in the structure and surface chemistry while simultaneously introducing defects, without compromising electrochemically active sites, are key factors for improving the rate performance of Ti3C2Tx. This study demonstrates improvement of the electrochemical performance of MXene electrodes by performing a controlled anodic oxidation. Good made better: Controllable anodic oxidation of 2D Ti3C2Tx improves the rate performance of supercapacitor electrodes. The capacitance retention at 2000 mV s−1 increases gradually from 38 % to 66 % by tuning the degree of anodic oxidation.